Interspecific hybrids between Paspalum plicatulum and P. oteroi: a key tool for forage breeding - Novo, Patricia Elda (2016)
Fil: Novo, Patricia Elda. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.